2022
DOI: 10.2352/j.percept.imaging.2022.5.000408
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Links between Colours and Tastes/Flavours

Abstract: The colour and other visual appearance properties of food and drink constitute a key factor determining consumer acceptance and choice behaviour. Not only do consumers associate specific colours with particular tastes and flavours, but adding or changing the colour of food and drink can also dramatically affect taste/flavour perception. Surprisingly, even the colour of cups, cutlery, plates, packages, and the colour of the environment itself, have also been shown to influence multisensory flavour perception. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…Different taste sensations are also found to be associated with different colors. Japanese colorist Kojiro Naito has experimentally concluded that sweet taste is associated with yellow, sour with green, bitter with black and salty with cyan (Spence & Levitan, 2022). According to research, children prefer sweet foods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different taste sensations are also found to be associated with different colors. Japanese colorist Kojiro Naito has experimentally concluded that sweet taste is associated with yellow, sour with green, bitter with black and salty with cyan (Spence & Levitan, 2022). According to research, children prefer sweet foods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of people will, for example, tend to agree that a red drink, or a red or pink color patch, looks (or is associated with) sweet rather than, say, sour (see Spence et al, 2015 , for a review of the literature on color-taste correspondences; Huisman et al, 2016 ; O’Mahony, 1983 ; Woods & Spence, 2016 ). It is, though, important to note that while consensual responses such as these are often obtained under such forced choice experimental conditions, this does not necessarily mean that the participants in the studies concerned thought that the stimuli that they paired together were perceptually similar to one another (see Spence & Levitan, 2022 , on this point). For example, people’s responses might instead merely reflect an expected, or predictive, relationship (i.e., associative learning), such as, for example, that if I see a red drink then I expect it to taste sweet (cf.…”
Section: Distinguishing Congruency From Similarity In the Case Of Th...mentioning
confidence: 99%
“…According toLafontaine et al (2020, p. 244): ' Associative learning is defined as learning about the relationship between two separate stimuli, where the stimuli might range from concrete objects and events to abstract concepts, such as time, location, context, or categories' .5 Here, already, one might start to wonder whether inferred colour-concept relations (seeTham et al, 2020) are as effective in terms of consumer perception/behaviour as the inferred mappings that are presumably often picked-up by the research (seeSpence & Levitan, 2022).…”
mentioning
confidence: 99%